Exploring Instructional Competencies of Mindanao State University-Sulu Teachers in the Age of COVID-19 Pandemic - Talikan, Allen I (HM Publisher, 2021)
This study investigated the instructional competencies of teachers in Mindanao State University-Sulu in the transition to alternative learning delivery methods in the age of the COVID-19 pandemic. The descriptive survey method was used in this study. The researcher used two sets of standardized questionnaires to obtain the necessary data including the respondents’ profiles. The profile of the teacher-respondents was determined using frequency count and percentage. Mean was used to analyze research questions. T-tests for independent samples and analysis of variance were used to test the stated hypotheses at a 0.05 level of significance. The following were the highlights of the study: (1) The common alternative learning delivery methods used by teachers were modules, Facebook, and Messenger; (2) The common instructional strategies of teachers were using Messenger for sending additional instructions on the lessons and other activities; entertaining questions from students through phone calls and text messages; and distributing printed module to students; (3) The level of instructional competencies of teachers is satisfactory; (4) There is no significant difference on teachers’ instructional strategies when they are classified according to their profile; (5) There is no significant difference on the level of teachers’ instructional competencies when they are classified according to gender and the college or high school where they teach; and (6) There is a significant difference on the level of teachers’ instructional competencies when they are classified according to age. The study recommended that the school administration should conduct intervention programs and policies on improving teachers’ competencies, especially in times of pandemic.